KETAHANAN PANGAN RUMAH TANGGA (HFIAS) SEBAGAI INDIKATOR DARI PEMENUHAN KERAGAMAN PANGAN (DDS) TERHADAP STATUS GIZI BALITA 12-59 BULAN - Nursyifa Rahma Maulida; Reni Fitriyani; Anna Fitriani (ARGIPA (Arsip Gizi dan Pangan), 2023)
The government of Indonesia is targeting an integrated reduction in nutrition problems. Household food security as one of the indicators of nutritional fulfillment in children both in quantity and quality is an interesting issue to see its relationship. This study aimed to see the relationship between food security and dietary diversity on the nutritional status of children aged 12-59 months in Cibaliung subdistrict, Pandeglang. The cross-sectional study was the design, and 98 children were selected purposively to be the sample. Household Food Insecurity Access Scale (HFIAS) was used to classify households in food security conditions. The two non-consecutive days of 24-hour recall method was used to obtain and classify dietary diversity scores based on WHO indicator. Data on nutritional status was obtained by measuring body weight and length/height as assessed by the z-score including Weight for Age, Height for Age, and Weight for Height z-score. The Chi-square test and Spearman Rank were used to see the relationship between variables. The result showed that the proportion of underweight is 27.6%, stunting is 44.9%, and wasting is 13.3%. There was a significant correlation between food security, and all indexed (p,0.05), WFA (r=0.491), HFA (r=0.416), and WFH (r=0.291). Other results showed the association between dietary diversity and nutritional status of WFA and WFH (p<0.05). The availability of food in the household is a determinant of fulfilling the intake which determines the nutritional status. So that, the interventions are needed to require the intake of children starting from the availability of food at the household level.